COORDINATION OF THE NATIONAL SECURITY SYSTEM OF THE UNITED KINGDOM (Annual of the Faculty of Philosophy in Skopje, 2008)
National security system of the United Kingdom is in great extent determined by the specifics of the very political system, by the historic circumstances, but also by the need to create a system which will be in function of protecting the countiy from contemporaiy risks and threats. The issues in the area of national defense in the United Kingdom are confined to the Queen, the Parliament and the Government with its cabinet. The three elements that constitute the legislative body, namely the Queen, the House of Lords and the House of Commons have been formed based on different principles. They rarely meet together and their meetings have symbolic significance. However, among these three elements, there is coordination, because it is required by the legislation, according to which all decisions should be first presented in front of the Queen.
Keywords: UNITED KINGDOM; INSTITUTIONS; NATIONAL POLICY; COORDINATION